Culture Shock Pada Mahasiswa Perantau Asal Jakarta Yang Berkuliah Di UIN Sunan Ampel Surabaya (Pengaplikasian Teori Differensiasi Budaya) - Hanafianto, Ahmad Dendy (Jurnal PUBLIQUE, 2023)
As overseas students, of course there are various things that are given special attention in the teaching and learning process in tertiary institutions. For overseas students, adapting to a new environment can be a challenge in itself. .To overcome culture shock, overseas students can take several steps such as getting to know a new environment better, looking for friends and study groups or communities. This type of research is qualitative using a phenomenological approach. this field. Qualitative research makes narrative data in the form of written terms or observed expressions and behavior. The theory of cultural differentiation is a sociological theory that explains how culture changes and how different cultures are formed in a society. After conducting interviews with several members of the Jabodetabek Regional Student Organization UIN Sunan Ampel Surabaya, the following facts and data were found. The first is that almost all students who are members of the Jabodetabek Regional Student Organization at UIN Sunan Ampel Surabaya experience culture shock due to cultural differences and the area from where they come from. Culture shock and the theory of cultural differentiation are closely related to the lives of overseas students from Jakarta who study at UIN Sunan Ampel Surabaya. The link between Culture Shock and the theory of cultural differentiation is that Culture Shock occurs because of the differences that exist between the original culture and the culture that has just been encountered.